2019
DOI: 10.1002/aet2.10413
|View full text |Cite
|
Sign up to set email alerts
|

The Case for Observation Medicine Education and Training in Emergency Medicine

Abstract: Background: Many hospitals have or will be opening an observation unit (OU), the majority managed by the emergency department (ED). Graduating emergency medicine (EM) residents will be expected to have the knowledge and skills necessary to appropriately identify and manage patients in this setting. Our objective is to examine the current state of observation medicine (OM) education and prevalence in EM training. Methods:In a follow-up to the 2019 Society for Academic Emergency Medicine (SAEM) OM Interest Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Observational medicine (OM) is an integral part of emergency medicine (EM), and according to Lily et al 1985, approximately 2.5% of trauma patients are admitted to the emergency department observational units (EDOU) [ 6 , 7 ]. The general purpose of EDOU, also known as clinical decision unit (CDU), short-stay unit (SSU), or emergency observation unit (EOU), is a short-term admission of patients for 24-hour observation and monitoring, and to ensure any essential urgent investigations or reviews [ 6 , 7 ]. This ensures adequate monitoring, comprehensive re-assessment, and safe discharge from the ED while avoiding unnecessary in-hospital admissions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observational medicine (OM) is an integral part of emergency medicine (EM), and according to Lily et al 1985, approximately 2.5% of trauma patients are admitted to the emergency department observational units (EDOU) [ 6 , 7 ]. The general purpose of EDOU, also known as clinical decision unit (CDU), short-stay unit (SSU), or emergency observation unit (EOU), is a short-term admission of patients for 24-hour observation and monitoring, and to ensure any essential urgent investigations or reviews [ 6 , 7 ]. This ensures adequate monitoring, comprehensive re-assessment, and safe discharge from the ED while avoiding unnecessary in-hospital admissions.…”
Section: Introductionmentioning
confidence: 99%
“…This ensures adequate monitoring, comprehensive re-assessment, and safe discharge from the ED while avoiding unnecessary in-hospital admissions. With respect to trauma patients, an EDOU plays an important role as a vast number of trauma patients do not need formal admission but benefit from a short EDOU admission [ 7 ]. These patients form a substantial subset of poly-trauma patients with low-to-moderate risk trauma, in whom it would be prudent to perform a comprehensive re-assessment prior to discharge to identify type I missed injuries.…”
Section: Introductionmentioning
confidence: 99%
“…2 Observation medicine (OM), therefore, encompasses the knowledge and skill needed to observe selected patients and actively manage them beyond the emergency department (ED), typically up to 24 hours. 3,4 The emergence of OM as a medical specialty parallels the growth of emergency medicine (EM). 5,6 The American College of Emergency Physicians, in its policy statement, reported that "observation of appropriate ED patients in a dedicated ED observation area, instead of a general inpatient bed or an acute care ED bed, is a 'best practice' that requires commitment of staff and hospital resources."…”
Section: Introductionmentioning
confidence: 99%
“…The Centers for Medicare and Medicaid Services defines observation care as “a specific, well-defined set of clinically appropriate services, which include ongoing assessment, reassessment, and short-term treatment; before a decision regarding further inpatient hospital management or discharge can be finalized.” 2 Observation medicine (OM), therefore, encompasses the knowledge and skill needed to observe selected patients and actively manage them beyond the emergency department (ED), typically up to 24 hours. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
“…Observation care, as defined by the Centers for Medicare and Medicaid Services (CMS), encompasses specific, clinically appropriate services that involve short-term treatment, assessment, and reassessment to determine the need for further hospital inpatient treatment or discharge [1][2][3][4][5]. Typically, patients placed under observation status stay for approximately 24 to 48 h [6][7][8].…”
Section: Introductionmentioning
confidence: 99%